2020
DOI: 10.3855/jidc.13246
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological trends of malaria in the Western regions of Saudi Arabia: a cross sectional study

Abstract: Introduction: Saudi Arabia has successfully reduced malaria cases to be constrained largely in the western regions. This study aimed to determine the epidemiological trends of malaria infection in five western regions of Saudi Arabia. Methodology: A retrospective analysis was conducted to investigate the epidemiological trends of malaria infection in the western regions, based on the published registry of the Saudi Ministry of Health, during the period from 2014 to 2017 using the appropriate statistical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 14 publications
2
5
0
Order By: Relevance
“…[3] The majority of malaria cases that were diagnosed in the current study due to infection with P vivax infection, followed by those caused by P falciparum. These findings have also been reported previously in Saudi Arabia [23] as well as India, [28] China. [29] In contrary, the previous reports documented P falciparum as the main causative agent of malaria in Saudi Arabia.…”
Section: Hassanein Et Al • Medicine (2023) Medicinesupporting
confidence: 90%
See 2 more Smart Citations
“…[3] The majority of malaria cases that were diagnosed in the current study due to infection with P vivax infection, followed by those caused by P falciparum. These findings have also been reported previously in Saudi Arabia [23] as well as India, [28] China. [29] In contrary, the previous reports documented P falciparum as the main causative agent of malaria in Saudi Arabia.…”
Section: Hassanein Et Al • Medicine (2023) Medicinesupporting
confidence: 90%
“…The present study identified 34 (6.89%) malaria cases among clinically suspected cases in Badr Governorate, Madinah Province, Saudi Arabia recruited from January 2021 through January 2022. In support, Amer et al, [ 23 ] have reported that Jazan has the highest frequent rate of malaria infection (66.3%) whereas Madinah (16.6%), Makkah (8.7%), Asir (7.4%) and Al-Bahah (1.0%) region, reflecting its endemicity with malaria in the Western regions of Saudi Arabia.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Mosquito-borne diseases are a significant health issue in KSA and several of these diseases have been documented in the country, including dengue fever, malaria, Rift Valley fever, and chikungunya [ 7 , 18 , 19 , 20 ]. In addition, WNV and Sindbis virus were isolated from mosquitoes in the country, demonstrating the potential for transmission [ 21 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies conducted worldwide and in KSA report that malaria mixed infections are not uncommon [5][6][7][8] . The majority of malaria studies in KSA were studies conducted in the Southwest area and included cases of mixed P.falciparum and P.vivax infections [9][10][11] .…”
Section: Discussionmentioning
confidence: 99%